Observations on the Frequency of Sightings of White Sharks in the Population of Gansbaai, South Africa, in the Presence of Cage Diving - Primo Micarelli; Francesca Romana Reinero; Antonio Pacifico; Gianni Giglio; Makenna Mahrer; Emilio Sperone (Biology)
Shark ecotourism is an ever-expanding reality, with hundreds of thousands of tourists involved annually. Although it represents a fundamental tool for sharing the urgent need to safeguard sharks with the public, the implications for the health and well-being of sharks must be taken into due consideration. In South Africa, cage-diving has been an important form of ecotourism since the 1990s. In Gansbaai, over a 14-year period from 2009 to 2024, excluding the 2020–2021 pandemic years, data was collected from cage diving operators’ boats on the frequency of sightings of white sharks. After approximately 560 h of field observations, averaging about 45 h per year and about 9 h per year between 2023 and 2024, 423 sharks were observed with five re-sightings. We highlighted that the number of sightings did not increase during the presence of cage diving operators and that site fidelity has not been observed by white sharks frequenting this area.